Vpliv etanola in njegovega metabolita acetaldehida na osrednji živčni sistem - Šarc, Lucija (Zdravniški vestnik, 2009)
Background Ethanol, a legal drug, is a big social problem in our country. First of all because of addiction development and also due to consequences of the chronic alcoholism. Ethanol effects to almost all organ systems. Consequences of its both, acute and chronic effects, are visible especially inthe central nervous system (CNS). Mechanisms of ethanol toxic effects have been already well researched. Lately, many studies attributed at least a part of ethanol effects to its first metabolite acetaldehyde which is produced, mainly with catalase, in the CNS. Acetaldehyde should have key role in the chronic ethilism development. Conclusions Effects of ethanol on the CNS are well known, and its main toxic mechanisms on the CNS have been getting more and more known/researched. Last studies showed that acetaldehyde alone shows effects similar to ethanol. Similar are also some known mechanism of acetaldehyde action. ĆThe most ethanol effects are consequence of its first metabolite actionĆ is still speculative statement, until it will be confirmed that such acetaldehyde effects could be developed by acetaldehyde concentrations accessible in the brain after individual drinking of ethanol.
Keywords: Acetaldehid; Acetaldehyde; Alcohol, Ethyl; Alcoholism; alkohol; Alkoholizem; Central Nervous System; Centralno živčevje; Drug Effects; etanol; ethanol; Fetal Alcohol Syndrome; Metabolism; metabolizem; osrednji živčni sistem; Plod, alkoholni sindrom; toksičnost; Toxicity